GNSS repeater-based spoofing heterogeneous antenna array with the analog nulling beamforming effect - Wang, Guanjun; Tang, Xusheng; Huang, Fengyi; Xia, Yulong; Ren, Qianyi (International journal of electronics and communications, 2025)
This paper proposes a novel heterogeneous antenna array consisting of a horizontally positioned top subarray and six evenly distributed side subarrays. Each subarray generates high-gain beams within its designated spatial solid angle, collectively enabling high-gain multi-beam coverage over the upper hemisphere. Combining the methods of sequential rotation arrays (SRAs) and sparse concentric ring arrays (CRAs), a quasi-concentric ring array (QCRA) is proposed to achieves excellent right-hand circularly polarized (RHCP) high-gain beams and low sidelobes, as well as effectively suppresses the grating lobe even beyond the limiting scanning angle. Different from the adaptive digital Minimum Variance Distortionless Response (MVDR) beamforming technology, which relies on high-speed digital processors, an analog nulling method closely integrating the simulated array model with the MVDR algorithm is developed to generate nulls in specified directions to suppress undesired satellite signals. Both simulated and experimental results confirm the array’s capability for wide elevation scanning (±85°) across both GPS L2 (1227.6 MHz) and L1 (1575.42 MHz) frequency bands. The measured RHCP gains reach 21.0 dBiC and 22.2 dBiC at L2 and L1 bands respectively, with fluctuations constrained below 1 dB and 2 dB, the axial ratio (AR) across all beam-steered directions remains below 1 dB. Accurate and effective nulls are achieved at the cost of a slight decline in gain (＜0.5 dB) with the MVDR algorithm employed.